Women on Boards and Firm Financial Performance: A Meta-Analysis - Post, Corinne; Byron, Kris (Academy of Management Journal, 2015)
Despite a large body of literature examining the relationship between women on boards and firm financial performance, the evidence is mixed. To reconcile the conflicting results, we statistically combine the results from 140 studies and examine whether these results vary by firms’ legal/regulatory and socio-cultural contexts. We find that female board representation is positively related to accounting returns and that this relationship is more positive in countries with stronger shareholder protections—perhaps because shareholder protections motivate boards to use the different knowledge, experience, and values that each member brings. We also find that, although the relationship between female board representation and market performance is near zero the relationship is positive in countries with greater gender parity (and negative in countries with low gender parity)—perhaps because societal gender differences in human capital may influence investors’ evaluations of the future earning potential of firms that have more female directors. Lastly, we find that female board representation is positively related to boards’ two primary responsibilities: monitoring and strategy involvement. For both firm financial performance and board activities, we find mean effect sizes comparable to those found in meta-analyses of other aspects of board composition. We discuss the theoretical and practical implications of our findings.